Pengaruh Penggunaan Teknologi Hidroponik Terhadap Minat Bercocok Tanam Siswa - Maghfiroh, Lailatul; Lianah, Lianah; Hidayatullah, Ahmad Fauzan (AL-HAYAT: Journal of Biology and Applied Biology, 2018)
The young generation is a development asset in the future, but many young people do not put their interest in cultivation. Especially the students of MA Manahijul Huda Ngagel who motivated by the low level of student interest on cultivation activities because the perception of students about farming is identical to the soil, dirty, requires a lot of energy, hot-pine under the sun and other things that make students reluctant to plunge In cultivation activities. The purpose of this research is to know the increase of farming interest of MA Manahijul Huda Ngagel Dukuhseti Pati students using hydroponic technology after treatment. The research method used in this research is qualitative by using descriptive analysis. The focus of this research is to focus on the interest of farming students through hydroponics. The data is taken with several methods, among others: observation, interview, questionnaire and documentation. The result of the research shows that the interest of farming students MA Manahijul Huda Ngagel Dukuhseti Pati increased after treatment, seen from the questionnaire value which increased by 6.03% from 79.17 to 85.2 with very good category. Increased interest in farming is also supported by the observation result of 12.4 with good category, interview and documentation that get the same result.